Kristalisasi Silika Xerogel dari Sekam Padi - M. Zamrun F; I. N. Sudiana (Universitas Halu Oleo, 2016)
The study to determine crystallinity of silica derived from rice husk ash during sintering by electric furnace and microwave was successfully performed. The crystallinity was determined by using X-Ray Diffraction for every sintering temperature step. The XRD analysis revealed that crystallinity of microwave sintered silica faster than that of electric furnace sintered ones. It indicates that the microwaves have affected atomic diffusion during sintering which result in enhancement of silica crystallization.